Profile of juvenile delinquents in the Regional Rehabilitation Center for the Youth RRCY (Region VI) in Guimaras - Calizo, Brian M .; Ocbeña, Ramir B. (2001.)
This study aimed to determine the profile of juvenile delinquents in RRCY VI in Guimaras. Respondents of the study were delinquents who were admitted in the rehabilitation center from November 15, 1998 to February 10, 2001. Interview schedules and questionnaires were the primary tools for gathering data. there were two sets of questionnaires using a five-point scale. The first set measured respondents' perception towards delinquency and second set measured their personal conviction to change. Two tailed test and Pearson Correlation were used to test the validity and reliability of the questionnaires respectively. Standard deviation was used to determine respondents' levels of perception towards delinquency and personal conviction to change. Results of the study showed that respondents have an average negative perception to wards delinquency and an average conviction to change. It was also found out that most of them are 14 to 17 years old, middle-born child who have low educational attainment, grave criminal offense/s. further, most of them came from big families, and at the same time intact. Lastly, most of them have parents whose occupations do not require any schooling or training to qualify.
Research Paper (Social Science 199.2). -- Miag-ao, Iloilo : University of the Philippines in the Visayas - College of Arts and Sciences, March 22, 2001.